KAJIAN TENTANG SIFAT FISIKA, KIMIA, DAN BIOLOGIS TANAH PERTANIAN YANG RENTAN LONGSOR DI LERENG BAGIAN BARAT GUNUNG LAWU WILAYAH KABUPATEN KARANGANYAR, JAWA TENGAH - Priyono - -; Kharis - Triyono; Martana - - (Innofarm:Jurnal Inovasi Pertanian, 2013)
ABSTRACT Research goals: to determine the qualitative and quantitative nature of the Agricultural Soil Landslide Prone on the slopes of the Western Region District Karanganyar Lawu Volcanic following   soil classification and the factors that affect soil formation. This research through a survey with primary data collection techniques in observation (boring and soil profile descriptions) as well as laboratory analysis of soil physical properties in particular.Place of research on landslide prone soils: Kec. Karangpandan / Ds Gerdu, district. Tawangmangu / Ds Plumbon, district.Ngargoyoso / Ds.Nglegok, district. Jatiyoso / Dsn Margorejo, district. Jenawi / Ds Seloromo, district. Kerjo / Ds Plosorejo. The time is August until October2011 In conclusion: 1). Regional District. Karanganyar including landslide-prone areas of the existing 17 districts there are 12 to 15 districts are prone to landslides So every time the rainy season there are certain areas affected by landslides, 2). Lawu as one important source of agricultural production in the district.Karanganyar; 3). Soil properties in the Regional District.Karanganyar quite fertile making it suitable for most agricultural business district areas. Karanganyar have properties and the same relative level of landslides (soil properties, geographic conditions, and weather); 4). The area around the avalanche (avalanche prone) still has good potential for farming as long as accompanied by environmentally sound land conservation efforts; 5). Soil Forming Factors that influence: climate, parent material (G. Lawu), and organisms (organic material and vegetation); 6). The results of soil classification obtained andosol name (PPT Bogor and FAO / UNESCO) or Hapludands (USDA Soil Taxonomy) for Ds.Plumbon Kec.Tawangmangu, and Kambisol (PPT Bogor and FAO / UNESCO) or Eutropepts (USDA Soil Taxonomy) for Ds. Plosorejo Kec.Kerjo, Ds. Nglegok district.Ngargoyoso, Ds Seloromo district. Jenawi, Dsn Margorejo district. Jatiyoso, Ds Gerdu district. Karangapandan., Key words: Assessment, Nature Landslide, Slope Mountain.